2001
DOI: 10.1210/mend.15.8.0674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat Shock Transcription Factor by GR

Abstract: The GR is a hormone-activated transcription factor that acts to regulate specific gene expression. In the absence of hormone, the GR and other steroid receptors have been shown to form complexes with several mammalian heat shock proteins. As heat shock proteins are produced by cells as an adaptive response to stress, speculation has existed that communication between the heat shock and glucocorticoid hormone signal pathways must exist. Only recently has evidence to support this hypothesis been reported. In alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…On the contrary, Hsp90 gene was upregulated by cortisol and then downregulated through the synthesized protein. In both cases a negative feedback mechanism could be invoked [45]. In other fish species, similar results have been reported [29,35] and it has been shown a quick time (15-90 min) for Hsp70 mRNA transcription [17] Differences in cortisol Hsp modulation reported in the literature [1,12,43] could be dependent on the organ and cell types examined in various fish species and/or by the experimental conditions.…”
Section: Discussionsupporting
confidence: 56%
“…On the contrary, Hsp90 gene was upregulated by cortisol and then downregulated through the synthesized protein. In both cases a negative feedback mechanism could be invoked [45]. In other fish species, similar results have been reported [29,35] and it has been shown a quick time (15-90 min) for Hsp70 mRNA transcription [17] Differences in cortisol Hsp modulation reported in the literature [1,12,43] could be dependent on the organ and cell types examined in various fish species and/or by the experimental conditions.…”
Section: Discussionsupporting
confidence: 56%
“…The in situ localization experiments in C. elegans described in the present paper demonstrate that DAF-21 is both a constitutive and a heatinduced protein. A recent study has shown that the major HSP (HSP70, 90 and 110) incur heat shock response through binding to heat shock factor-1 and that glucocorticoids regulate signaling (Wadekar et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of the samples to Immobilon-P ® membranes (Millipore Corp.) and quantitative immunoblotting were performed as described previously (8,11). The BuGR2 monoclonal antibody against GR (Affinity Bioreagents) was used to probe for receptor, and various antibodies were used to probe for Hsp90 (H38220, Transduction Laboratories, Inc.), FKBP52 (UPJ56 (12)), FKBP51 (PA0-021, Affinity Bioreagents), and dynein intermediate chain (monoclonal antibody 1618, Chemicon International, Inc.).…”
Section: Methodsmentioning
confidence: 99%